Incidence and implications of a left inferior vena cava on IVC filter placement - Kalyanpur, A; Pollak, JS (Indian Journal of Radiology and Imaging, 2005)
Objective: To assess the prevalence and ability to detect a left inferior vena cava (IVC) during venography prior to filter placement and its implications for device implantation. Materials and Methods : Over 58 months, patients referred for an IVC filter were prospectively evaluated for a left IVC by performing cavography injecting into the left iliac vein, left renal venography, or CT scan correlation. Additionally, cavograms of patients receiving filters over the four previous years were reviewed to assess the adequacy of detecting these anomalies based on the degree of opacification of the left iliac vein in relation to the position of the catheter tip. Results: Prospective evaluation for a left IVC was adequate in 477 of 503 patients. Retrospective evaluation using CT scans was possible in another 14. Left IVCs were detected in 5 patients (1%). Three patients with duplications were managed with either 2 filters, a suprarenal filter, or a bird′s nest filter straddling both cavas. Two patients with isolated left IVCs received a single filter. Of 62 retrospectively reviewed cavograms, the left iliac vein was inadequately opacified in 69% when the catheter was in the low IVC (53 patients) and 71% when it was in the right iliac vein (7 patients). Conclusions: Low caval or right iliac vein injections infrequently provide sufficient reflux into the left iliac vein to assess for a left IVC. Left iliac vein catheterization is easy and will readily provide this information. Modifications in filter placement technique may be necessary when caval anomalies are present.
Keywords: Left IVC; IVC filter